The Special Metaphysics of Pietro Pomponazzi - Buganza, Jacob (Anales del Seminario de Historia de la Filosofía, 2026)
This work recovers the main positions, and the arguments on which the special metaphysics of Pietro Pomponazzi is based. This metaphysics takes shape in anthropological and theological themes, that is, about the soul, free will and predestination. In the opinion of scholars such as Martin Pine, Pomponazzi represents the most radical Renaissance Aristotelianism. However, as demonstrated in the work, the Mantuan philosopher continues to declare his adherence to the teaching of the Church, even when he cannot combine it with rationality.
Keywords: metaphysics; Renaissance Aristotelianism; Pomponazzi; soul; free will; predestination